FORMATION OF SOCIAL INVESTMENT BUDGET IN ACCORDANCE WITH STATE INVESTMENT POLICY - Andrey A. Derkach (Статистика и экономика, 2016)
Problems of formation of Social investment budget in accordance with reasonable standards and effective demand of social facilities have been reviewed in this article.